Pengaruh Model Project Based Learning dan Motivasi Belajar terhadap Keterampilan Menulis Teks Prosedur Siswa SMP - Fauziati Fauziati; Syofiani Syofiani; Yetty Morelent (Lembaga Yasin AlSys, 2026)
Although writing skills occupy a central position in the Kurikulum Merdeka, students’ ability to produce procedural texts remains limited due to teacher-centred instructional methods and low learning motivation. This study aimed to analyze the effects of the Project-Based Learning (PjBL) model and learning motivation on procedural text writing achievement among Phase D, Grade VII students at UPT SMP Negeri 1 Pulau Punjung, as well as to examine the interaction between these variables. A quantitative approach was employed using a quasi-experimental method with a nonequivalent control group design. The sample was determined through cluster random sampling, resulting in one experimental class taught using PjBL and one control class taught using conventional instruction. Data were collected through a performance test in writing procedural texts and a learning motivation questionnaire, and analyzed using t-tests and ANOVA. The findings showed that PjBL had a significant effect on improving procedural text writing skills, with the experimental class achieving a mean score of 88.21, higher than the control class mean of 73.06 (t = 7.530 > t_critical = 2.002). Among highly motivated students, the experimental class mean score of 85.21 also exceeded the control class mean of 77.00 (t = 4.488 > t_critical = 2.048), whereas among low-motivation students, the experimental class mean score of 91.21 surpassed the control class mean of 68.87 (t = 7.113 > t_critical = 2.052). In addition, there was a significant interaction between the instructional model and learning motivation (F = 56.698 > F_critical = 4.01), indicating that the effectiveness of PjBL was reinforced across different motivation levels. The study concludes that implementing PjBL effectively enhances procedural text writing skills through contextual, project-oriented learning experiences and underscores the importance of integrating active learning strategies with motivation management within the framework of the Kurikulum Merdeka. The implications include theoretical contributions to project-based writing pedagogy and practical recommendations for teachers and educational institutions to design teaching modules that are adaptive to students’ psychological profiles, while opening avenues for further research on the use of digital media in PjBL for other text genres.